Coupled lattice Boltzmann–discrete element simulations of bed load sediment transport - Vu, Duc Chung; Vo, Thanh-Trung (Vietnam Journal of Mechanics, 2026)
The transport of granular bed under fluid flow involves erosion, entrainment, and deposition processes, that are fundamental to both geophysical and engineering systems. This study presents numerical simulations of bed load sediment transport induced by turbulent shear flow using a two-dimensional coupled framework that combines the lattice Boltzmann method (LBM) for the fluid phase with the discrete element method (DEM) for granular dynamics. A multiple-relaxation-time LBM is developed to enhance numerical stability without significantly increasing computational cost. First, the model is validated against two classical benchmark tests, showing excellent agreement with the analytical and numerical references. Subsequently, simulations of a polydisperse granular bed reveal three distinct regions: a bedload layer, where particles roll and slide at low velocities through frictional contacts; a saltation layer, where particles are intermittently lifted and redeposited; and a suspension layer, where particles are transported by the flow, with their velocities approaching the maximum fluid velocity. Furthermore, the force-chain structure in the bedload layer is analogous to that observed in dry granular packing under simple shear, despite the differences in particle shape. The simulations data further demonstrate size-dependent segregation within the bedload layer, driven by shear-induced particle interactions.